Assessing health-care needs of patients with diabetes in Iran's health-care system: A modified delphi method study - Malihe Sadat Moayed; Behnaz Amoozadeh; Akram Parandeh (Journal of Education and Health Promotion, 2020)
INTRODUCTION: Due to the increasing prevalence of diabetes in the world, the assessment of the patient needs is essential. Understanding the needs of patients will play a very important role in providing an effective training program for patients. This study aimed to explain the health-care needs of patients with diabetes in Iran's health-care system. MATERIALS AND METHODS: The present study was conducted using a modified Delphi technique in three rounds in 2017–2018. In the first round, patients' needs were extracted based on qualitative interviews and a review of the literature. Then, the second and third rounds were determined through surveys, achieving maximum consensus and grading the importance of the patients' basic needs. Participants selected using purposeful sampling and included 58 diabetes patients, family, and providers of the health system who were referred to urban health centers, rural, and one of the clinics of Darreh Shahr, Ilam Province. For data analysis, qualitative content analysis was used in the first Delphi round and descriptive statistics were used in the second and third rounds. RESULTS: Regarding health-care needs of patients with diabetes, four main themes included: information and knowledge needs, need for reinforcement/reform of religious-cultural beliefs, need for health self-management, and ultimately supportive needs have emerged. CONCLUSIONS: According to the results, before designing and developing effective educational programs, the need assessment to improve knowledge, correcting unrealistic attitudes and beliefs, as well as modifying their self-care behaviors and performance in preventing diabetes is recommended.